2021
DOI: 10.1002/jssc.202100751
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly efficient in‐tube solid‐phase microextraction system coupled with UHPLC‐MS/MS for analyzing trace hydroxyl polycyclic aromatic hydrocarbons in biological samples

Abstract: Hydroxyl polycyclic aromatic hydrocarbons are considered active mutagenic and carcinogenic substances and are found in extremely low levels (ng/g) in biological samples. As a result, their determination in urine and blood samples is challenging, and a sensitive and effective method for the analysis of trace hydroxyl polycyclic aromatic hydrocarbons in complex biological matrices is required. In this work, a novel macroporous in-tube solid-phase microextraction monolith was prepared via a thiol-yne click reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The median levels were 0.12 ng/mL in the exposed group and 0.031 ng/mL in the control group. The OH-AntQ levels in the control group were consistent with an early study that reported comparable levels in smokers’ and nonsmokers’ urine samples (0.039 and 0.034 ng/mL, respectively) . However, the levels of OH-AntQ were higher in the exposed group than in smokers’ and nonsmokers’ groups.…”
Section: Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The median levels were 0.12 ng/mL in the exposed group and 0.031 ng/mL in the control group. The OH-AntQ levels in the control group were consistent with an early study that reported comparable levels in smokers’ and nonsmokers’ urine samples (0.039 and 0.034 ng/mL, respectively) . However, the levels of OH-AntQ were higher in the exposed group than in smokers’ and nonsmokers’ groups.…”
Section: Results and Discussionsupporting
confidence: 87%
“…The current work also unveiled several novel metabolites, including indoxyl (3-OH-Ind), 4-hydroxyindole (4-OH-Ind), quinolin-2-ol (2-OH-QNL), 2-hydroxydibenzofuran (2-OH-DBF) and its isomers, and hydroxyanthraquinone (OH-AntQ). These compounds were identified as metabolites of HPAHs incubated by human cells in vitro or via rat experiment. , In this study, 3- and 4-OH-Ind and 2-OH-QNL were detected in human urine for the first time, while 2-OH-DBF and OH-AntQ had only been reported in a handful of studies. , These compounds show potential as biomarkers for occupational exposure at coking sites. However, it is important to note that some of their parent compounds such as quinoline (QNL) and anthraquinone (AntQ) have been classified as possible human carcinogens by the International Agency for Research on Cancer, indicating that exposure to these pollutants could pose a potential health risk to humans.…”
Section: Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To date, the determination of OH-PAHs in human samples has been widely addressed in urine [5][6][7][8][9][10]. Other human samples studied have included serum [11], hair [12], and fingernails [13].…”
Section: Introductionmentioning
confidence: 99%
“…A review on the electrochemical analysis of the analyte has been recently published [10]. UHPLC is another analytical technique that has gained popularity in recent years in the field of pharmaceutical, clinical and toxicological analysis [11][12][13]. Compared to the traditional HPLC technique, it can effectively contribute to the reduction of organic solvent consumption and analysis cost which complies with the principles of Green Analytical Chemistry [14,15].…”
Section: Introductionmentioning
confidence: 99%